A Novel and Green Method for the Synthesis of Benzo-15-crown-5 Containing Sulphonylthiourea-Based Receptors - Ding, Cong-Wen; Zhang, Yue-Feng; Yu, Hai-Feng (Asian Journal of Chemistry, 2013)
The nucleophilic reaction of 4'-aminobenzo-15-crown-5 and carbon disulphide in aqueous KOH afforded corresponding dithiocarbamate salt. Subsequent nucleophilic substitution reactions with sulfonamides aqueous NaOH provided benzo-15-crown-5-containing sulphonylthioureas. This novel, green method has the advantages of simple operation, high yields, easy product-isolation and environmental friendliness.